Pengaruh Self Compassion terhadap Psychological Well Being pada Mahasiswa Bimbingan dan Konseling - Merdika, Natasya; Moesarofah, Moesarofah (Jurnal Simki Pedagogia, 2025)
Self Compassion and Psychological Well Being which aims as an attitude of kindness to oneself in facing various difficulties, which is needed by Guidance and Counseling Students. Using a quantitative approach cross-sectional design. Data were collected through 2 types of measurement scales, namely the Self Compassion Scale and the Psychological Well Being Scale, using the Simple Random Sampling technique to select 132 respondents randomly from 160 populations, the results of the analysis with the Spearman test showed 0.000 because the Sig. value. (2-tailed) <0.05, indicating a strong influence. The findings of this study are useful for guidance and counseling services on campus in the application of Self Compassion to Psychological Well Being in Guidance and Counseling Students.